Autoinducer-2 May Be a New Biomarker for Monitoring Neonatal Necrotizing Enterocolitis - Fu, Chun-Yan; Li, Lu-Quan; Yang, Ting; She, Xiang; Ai, Qing; Wang, Zheng-Li (Frontiers in Cellular and Infection Microbiology, 2020)
Autoinducer-2 (AI-2) has a widely accepted role in bacterial intra- and interspecies communication. Little is known about the relationships between AI-2 and NEC. This study found that AI-2 levels in patients and in a NEC mouse model were detected using the Vibrio harveyi BB170 assay system. Bacterial communities of the newborns' stool microbiota (NEC acute group, NEC recovery group, control group, and antibiotics-free group) and of the NEC mouse model (NEC group and control group) were detected by high-throughput sequencing. Intestinal histopathological changes were observed after HE staining. The AI-2 level in the NEC acute group (44.75 [40.17~65.52]) was significantly lower than that in the control group, NEC recovery group and antibiotics-free group. The overall microbiota compositions of each group at the phylum level were not significantly different. The proportions of Enterococcus, Clostridium_sensu_stricto_1, Peptoclostridium, and Veillonella had significant differences among the 4 groups at the genus level. In animal experiments, the AI-2 level in feces of NEC mice (56.89 ± 11.87) was significantly lower than that in the feces of control group mice (102.70 ± 22.97). The microbiota compositions of NEC and control group mice at the phylum level were not significantly different. At the genus level, Klebsiella, Clostridium_sensu_stricto_1, and Peptoclostridium abundances in the NEC group increased significantly compared with those in the control group (P < 0.05). In addition, Lactobacillus, Pasteurella, and Parabacteroides abundances in the NEC group decreased significantly compared with those in the normal control group (P < 0.05), while Lactobacillus, Pasteurella, and Parabacteroides abundances had the opposite trend. The AI-2 concentration decreased significantly in the acute phase of NEC and increased gradually in the convalescent phase. We conclude that the concentration of AI-2 was correlated with intestinal flora disorder and different stages of disease. AI-2 may be a new biomarker for the diagnosis and monitoring of NEC. Trial Registry: ClinicalTrials.gov; ChiCTR-ROC-17013746; URL: www.clinicaltrials.gov